Pin-point denitrification for groundwater purification without direct chemical dosing: Demonstration of a two-chamber sulfide-driven denitrifying microbial electrochemical system. (1st September 2020) - Lin, Sen; Hao, Tianwei; Li, Xiling; Xiao, Yihang; Chen, Guanghao
Abstract: The nitrate concentration in groundwater has been increasing over time due to the intensive use of nitrogen fertilizer. Current nitrate removal technologies are restricted by the high operational cost or the inevitable secondary contaminations. This study proposed a two-chamber sulfide-driven denitrifying microbial electrochemical system to denitrify nitrate in its cathode chamber. Instead of conventional organic substrates, sulfide is oxidized in the anode chamber to generate electrons for cathodic denitrification. Long-term performance of this novel system was evaluated over 200 days (100 cycles) of batch-fed operation. With the assistance of anodic microorganisms, sulfide can be directly oxidized to sulfate thus avoiding passivating the anode. Catalyzed by the cathodic microorganisms, complete denitrification was realized with neither nitrite nor nitrous oxide accumulation. Benefiting from the electroautotrophic behavior of the functional microorganisms, high electron utilization efficiencies were achieved, 80% and 85% for the anode (sulfide oxidation) and the cathode (denitrification) respectively. Both observed electrode potentials and microbial analyses revealed that cytochrome c is the crucial electron transfer mediator in the cathodic electron transfer for denitrification. Based on the analysis of planktonic and biofilm microbial samples, anodic and cathodic extracellular electron transfer bioprocesses are proposed, both the direct and mediated electron transfers involved, as were revealed by immobilized and planktonic functional microorganisms, respectively. This study demonstrates the feasibility of purifying nitrate-contaminated groundwater without sacrificing its water quality in a separate mode of treatment. This concept can be extended to a broader field, in which the water requires bio-polishing without introducing unwanted secondary pollution like the post-denitrification of wastewater effluents. Graphical abstract: Image 1 Highlights: Pin-point denitrification of groundwater was achieved without direct chemical dosing. Sulfide was used as anodic electron donor to obtain high electron utilization efficiency. Cytochrome c was identified as the crucial extracellular electron carrier for cathodic denitrification. A system consisting of both direct and mediated extracellular electron transfer is proposed.